Strategi Redaksi Harian Parepos Menarik Minat Pembaca Melalui Perwajahan Halaman Satu - Suhartina Suhartina; Rasmika Rasmika; Iskandar Iskandar (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
This research aims to describe 1) the layout of the daily newspaper "Parepos" in attracting readers' interest and 2) the strategies employed in the layout of the daily newspaper "Parepos" to attract readers' interest. The research conducted is of a qualitative nature with a study of narrative descriptive analysis. The data collection techniques used include observation, documentation, and interviews with the editorial team and journalists who meet the research criteria. The data analysis technique used is the narrative descriptive approach developed by Miles and Huberman, which involves three stages: data reduction, data presentation, and drawing conclusions.The research findings indicate that "Parepos" applies graphic or visual elements accompanied by accurate data, places headlines in the center, positions feature news at the bottom of the newspaper, and places profile or personality news on the side of the newspaper. The strategies employed are 1) emphasizing certain layout characteristics, 2) designing the layout through careful planning, 3) presenting flexible layout content, and 4) conducting periodic evaluations.